Long COVID symptoms 6 months after acute infection among people living with HIV and people not living with HIV - Qin Li; Qin Li; Yijie Ma; Peng He; Dongqiong Chen; Tingrui Zhang; Xiaoying Wang; Ying Xu; Peiming Li; Weibo Wen; Weibo Wen; Zefeng Wang (Frontiers in Immunology)
BackgroundChronic viral infections, such as Human Immunodeficiency Virus (HIV), and their reactivation are considered potential contributing factors to Long-Corona Virus Disease (LC). However, research on the long-term sequelae of Long-COVID in individuals with HIV is limited.MethodsWe conducted a case-control study involving a total of 84 participants categorized into two groups: people living with HIV (PLWH) and people not living with HIV (PNLWH) within the six-month post-infection LC population. Differences in sequelae symptoms, cardiovascular biomarkers (VCAM-1, ICAM-1, and ACE2), Severe Acute Respiratory Syndrome Coronavirus 2 neutralization antibodies (SARS-CoV-2 nAb) and cytokines (IFN-γ, IL-6, and IL-17) were analyzed between the two groups.ResultsAfter 6 months of infection, PLWH exhibited significantly higher serum levels of ACE2, VCAM-1, and ICAM-1 (P < 0.01, respectively) compared to PNLWH with COVID-19. Additionally, sequelae symptoms were more pronounced in PNLWH, and there were no differences in serum levels of IFN-γ, TNF-α, IL-6, and IL-17 between the two groups (P > 0.05, respectively).ConclusionPLWH had lower symptoms of LC and reduced frequency of symptoms, increased cardiovascular risk factors, and no differences in levels of inflammation or SARS-CoV-2 nAb levels when compared to PNLWH.